2009
DOI: 10.1021/la902962g
|View full text |Cite
|
Sign up to set email alerts
|

Transport Effects in the Electrooxidation of Methanol Studied on Nanostructured Pt/Glassy Carbon Electrodes

Abstract: Transport effects in the methanol oxidation reaction (MOR) were investigated using nanostructured Pt/glassy carbon (GC) electrodes and, for comparison, a polycrystalline Pt electrode. The nanostructured Pt/GC electrodes, consisting of a regular array of catalytically active cylindrical Pt nanostructures with 55 +/- 10 nm in diameter and different densities supported on a planar GC substrate, were fabricated employing hole-mask colloidal lithography (HCL). The MOR measurements were performed under controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 62 publications
8
55
2
2
Order By: Relevance
“…These measurements exhibited a clear correlation between the product distribution and the density of the Pt ultra-microelectrodes, with the relative amount of reaction intermediates in the overall reaction products decreasing with increasing density of catalytically active Pt nanodisks [5,7]. Similar trends have been reported for the oxidation of formaldehyde [10] and methanol [11] on these nanostructured Pt/GC electrodes. The same is true for the dependency of the product yields on the catalyst loading in the case of a single large Pt/C electrode, e.g.…”
Section: Introductionsupporting
confidence: 76%
“…These measurements exhibited a clear correlation between the product distribution and the density of the Pt ultra-microelectrodes, with the relative amount of reaction intermediates in the overall reaction products decreasing with increasing density of catalytically active Pt nanodisks [5,7]. Similar trends have been reported for the oxidation of formaldehyde [10] and methanol [11] on these nanostructured Pt/GC electrodes. The same is true for the dependency of the product yields on the catalyst loading in the case of a single large Pt/C electrode, e.g.…”
Section: Introductionsupporting
confidence: 76%
“…A few half-cell studies are available on the effect of mass transport upon alcohol oxidation over Pt, but these have concentrated on the utilisation of methanol as a fuel [38,41,42,[47][48][49] with very few studies using ethanol [39,50,51]. Most studies have reported a suppression of the extent of oxidation of methanol on Pt disk electrode with increased mass transport [38,42].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…tion [13,14] ). However, pronounced mass transport effects on the reaction selectivity were demonstrated recently for electrocatalytic reactions over nanostructured Pt electrodes [15][16][17][18] deposited onto a planar glassy carbon substrate by employing colloidal lithography techniques. [19,20] On these surfaces, mass transport effects can be assessed in model studies where the reactant delivery to the patterned surface and off-transport of the reaction intermediates/products are varied in a controlled way, thus affecting both reaction activity and selectivity, as probed for several electrocatalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] On these surfaces, mass transport effects can be assessed in model studies where the reactant delivery to the patterned surface and off-transport of the reaction intermediates/products are varied in a controlled way, thus affecting both reaction activity and selectivity, as probed for several electrocatalytic reactions. [15][16][17][18] Complementary galvanostatic formaldehyde oxidation measurements on these patterned catalysts are the topics herein. Since the galvanostatic oxidation of formaldehyde on continuous electrodes exhibits potential oscillations, [21][22][23][24][25][26] such studies will also yield information about synchronization properties of the array of individual Pt nanostructures (oscillators), that is, whether the array will exhibit a regular concerted oscillatory behavior, or whether the individual oscillators will behave randomly, resulting in a stationary response of the average electrode potential.…”
Section: Introductionmentioning
confidence: 99%